From Immigrants to Americans: Race and Assimilation during the Great Migration - Vasiliki Fouka; Soumyajit Mazumder; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
How does the arrival of a new minority group affect the social acceptance and outcomes of existing minorities? We study this question in the context of the First Great Migration. Between 1915 and 1930, 1.5 million African Americans moved from the US South to Northern urban centers, which were home to millions of European immigrants arrived in previous decades. We formalize and empirically test the hypothesis that the inflows of Black Americans changed perceptions of outgroup distance among native-born whites, reducing the barriers to the social integration of European immigrants. Predicting Black in-migration with a version of the shift-share instrument, we find that immigrants living in areas that received more Black migrants experienced higher assimilation along a range of outcomes, such as naturalization rates and intermarriages with native-born spouses. Evidence from the historical press and patterns of heterogeneity across immigrant nationalities provide additional support to the role of shifting perceptions of the white majority.
Keywords: J11; J15; N32; 330; immigration; assimilation; Great Migration; race; group identity